Severe intimate partner violence is associated with all-cause mortality among women living with HIV. (1st August 2020) - Closson, Kalysha; McLinden, Taylor; Parry, Rebeccah; Lee, Melanie; Gibbs, Andrew; Kibel, Mia; Wang, Lu; Trigg, Jason; Braitstein, Paula; Pick, Neora; Parashar, Surita; Montaner, Julio S.G.; et al.
Abstract : Objective: To examine the independent association between intimate partner violence (IPV) severity and all-cause mortality among women living with HIV (WLHIV). Design: Cross-sectional questionnaire linked to longitudinal vital statistics data. Methods: We examined the lifetime prevalence of IPV and age-standardized all-cause mortality rates by IPV severity reported by WLHIV. Lifetime IPV (emotional/verbal, physical, or sexual) severity was assessed as a categorical variable: no history of any IPV (none); experienced one or two forms of IPV (moderate); or experienced all three forms of IPV (severe IPV). Two separate logistic regression models examined associations between any IPV (vs. none) as well as IPV severity (none vs. moderate, severe) and all-cause mortality. Results: At the time of interview (2007–2010), 260 participants self-identified as women with a median (Q1–Q3) age of 41 years (35–46). Of these women, the majority were unemployed (85%), 59% reported any IPV and 24% reported severe IPV. Of the 252 women followed until 31 December 2017, 25% ( n = 63) died. Age-standardized all-cause mortality rates for WLHIV who experienced severe IPV were two-times higher than women with no history of IPV (44.7 per 1000 woman-years vs. 20.9 per 1000 woman-years). After adjustment for confounding, experiences of severe IPV (vs. none) were significantly associated with all-cause mortality (aOR = 2.42, 95% CI = 1.03–5.70). Conclusion: Although we found that any lifetime experience of IPV was not associated with all-cause mortality, women ever experiencing severe IPV were significantly more likely to die during the study period. This may suggest a need for increased trauma- and violence-aware approaches.